Effect of Soil Amendment Application on Productivity of Watermelon (Citrullus vulgaris Schard.) in Suboptimal Land - Tri Mulya Hartati; Krishna Aji; Amiruddin Teapon; Urai Suci Yulies Vitri Indrawati (Jurnal Ilmu Pertanian Indonesia, 2026)
Inappropriate land management system has emerged as a serious issue in agricultural development. Instead of boosting land productivity, suboptimal land use has become a viable option for regional agricultural development. However, this has not resulted in considerable increases in agricultural productivity. The purpose of this study was to improve soil parameters and increase watermelon (Citrullus vulgaris Schard) production by applying soil amendments to suboptimal land. This study was conducted utilizing a factorial randomized group design with two factors. The first factor was the application of mulch (M) with three treatment levels: M0 = no mulch, M1 = reed mulch, and M2 = coconut leaf mulch; the second factor was the application of bird manure fertilizer (P) with three treatment levels: P0 = no fertilizer, P1 = 10 t/ha fertilizer, and P2 = 20 t/ha. The data was analyzed using ANOVA and Duncan's multiple range test (significant at P < 0.05). The study was conducted at Khairun University's Campus IV in Madihutu Village, Kao Teluk District, North Halmahera Regency. Soil parameters and plant agronomic traits were among the observed variables. The findings revealed that the mulch and bird manure treatments had no significant impact on soil characteristics. In terms of plant agronomic features, the mulch-free treatment had the greatest impact on watermelon plant growth and yield, whereas the 10 t/ha fertilizer treatment outperformed the other treatments. Keywords: bird manure fertilizer, mulch, suboptimal land, watermelon plant